NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL PAK GURU KARYA AWANG SURYA DAN NOVEL AYAH KARYA ANDREA HIRATA - Rohmat Hadi Kuswoyo (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
The purpose of this study was to determine the values of character education relationship with God, themselves, the social environment in the novel Pak Guru by Awang Surya and novel Ayah by Andrea Hirata. Sources of the data in this research are the values of character education contained in the both of the novel. The results showed that the values contained in the novel character education novel Pak Guru by Awang Surya and novel Ayah by Andrea Hirata. first, consisting of the values of character education relationship with God. Second, they are also contains the values of character education to do with themselves. Third, they are also contains the values of character education to do with the social environment.